THE NY FRIESLAND OROGEN, SPITSBERGEN - Harland W.B.; Scott R.A.; Auckland K.A.; Snape I. (My University, 1992)
The Caledonides of Ny Friesland comprise the type Hecla Hoek sequence of Svalbard, a succession of late Proterozoic to Ordovician strata greater than 18 km thick. Three supergroups constitute the sequence: the Stubendorffbreen Supergroup (Riphean), the Lomfjorden Supergroup (late Riphean-Sturtian) and the Hinlopenstretet Supergroup (Varanger-mid-Ordovician). Basement elements have recently been identified within the Stubendorffbreen Supergroup, but their extent and significance is yet to be established. The Stubendorffbreen Supergroup records the deposition of sediments and volcanics (both acid and basic) in an unstable marine environment. In contrast, the Lomfjorden and Hinlopenstretet supergroups record sedimentation in a shallow-marine, periodically emergent, stable environment without volcanism. The Ny Friesland Orogen is divided into two subterranes by the Veteranen Line, a zone of attenuation along which sinistral strike-slip displacement has occurred. This line separates the strongly deformed Stubendorffbreen Supergroup rocks in the west from the less-intensely deformed Lomfjorden and Hinlopenstretet supergroup rocks in the east. Despite these contrasts and the obvious displacement, there is no evidence that a significant stratigraphie break occurs across it. All the supergroups were deformed and metamorphosed during the late Ordovician-Silurian Ny Friesland Orogeny. Early compressional deformation produced isoclinal folding and nappes in the Stubendorffbreen Supergroup rocks, accompanied by amphibolite faciès metamorphism; deformation in the Lomfjorden and Hinlopenstretet supergroups was less intense with open, upright folds and greenschist or subgreenschist facies metamorphism. Early compression was followed by a Silurian transpressive deformation that generated a pervasive lineation in the Stubendorffbreen Supergroup rocks. Transpressive deformation and the associated sinistral strike-slip was focused where strata were in a near-vertical attitude conducive to displacement. At a late stage in the orogeny, and probably still under a strike-slip regime, batholiths were emplaced into rocks east of the Veteranen Line. As a result of continued sinistral displacement (transpression, transcurrence and transtension) along the Billefjorden Fault Zone, Ny Friesland (part of the Eastern Province of Svalbard) finally docked against the Central Province during the late Devonian Svalbardian movements. At the same time, the Central Province docked against the Western Province. In total, hundreds of kilometres of Caledonian displacement along the Billefjorden Fault Zone brought the Eastern and Central provinces into their present positions. Pre-Carboniferous Svalbard is thus a composite terrane of at least three provinces, each comprising more than one minor terrane.
Keywords: Carboniferous; Riphean; Ordovician; Silurian; Devonian; Proterozoic; Докембрий::Протерозой::Рифей; Paleozoic::Ordovician; Precambrian::Proterozoic; Paleozoic::Carboniferous; Paleozoic::Devonian; Paleozoic::Silurian; Precambrian::Proterozoic::Riphean; Палеозой::Ордовикская; Палеозой::Каменноугольная; Палеозой::Девонская; Палеозой::Силурийская; Докембрий::Протерозой